2017
DOI: 10.1016/j.jconrel.2017.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to enhance the distribution of nanotherapeutics in the brain

Abstract: Convection enhanced delivery (CED) provides a powerful means to bypass the blood-brain barrier and drive widespread distribution of therapeutics in brain parenchyma away from the point of local administration. However, recent studies have detailed that the overall distribution of therapeutic nanoparticles (NP) following CED remains poor, due to tissue inhomogeneity and anatomical barriers present in the brain, which has limited its translational applicability. Using probe NP, we first demonstrate that a signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 51 publications
2
28
0
Order By: Relevance
“…26 13,70,71 Nanoparticle diffusive ability also plays a role in reaching target microglial cells and in achieving maximal therapeutic impact. 72,73 As evidenced by the MPT results after OGD, PS-PEG nanoparticles exhibited more than 16-fold higher diffusive ability compared to the NC condition. In this study, we directly confirmed diffusivity of PS-PEG, but PEGylated QDs and PAMAM dendrimers have also been shown to move effectively within the brain parenchyma.…”
Section: Discussionmentioning
confidence: 94%
“…26 13,70,71 Nanoparticle diffusive ability also plays a role in reaching target microglial cells and in achieving maximal therapeutic impact. 72,73 As evidenced by the MPT results after OGD, PS-PEG nanoparticles exhibited more than 16-fold higher diffusive ability compared to the NC condition. In this study, we directly confirmed diffusivity of PS-PEG, but PEGylated QDs and PAMAM dendrimers have also been shown to move effectively within the brain parenchyma.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, more BSA/Mal‐SPIONs would stay in the extracellular circulation system and diffuse to other brain areas through the perivascular flow pathway. Because of their decreased nonspecific cell internalization, BSA/Mal‐SPIONs are more likely to be removed by the efflux pump that exists in blood‐brain barrier (BBB) (Jia et al, ) to maintain and regulate the homeostatic balance in the brain (Iliff et al, ; Zhang et al, ). On the other hand, albumin that is not naturally found in brain parenchyma has been reported to induce immunoreactivity in the brain (Kozai, Jaquins‐Gerstl, Vazquez, Michael, & Cui, ), and some BSA/Mal‐SPIONs are found in glial cells in the present work.…”
Section: Discussionmentioning
confidence: 99%
“…hydrophobic and negatively charged) and steric diffusional barrier, and established design criteria for engineering nanoparticle-based therapeutic delivery systems that can efficiently spread through the ECM [5][6][7]. Specifically, we found that nanoparticles with diameters small enough (≤ ~110 nm) to fit through the ECM pores while possessing non-adhesive dense surface polyethylene glycol (PEG) coatings rapidly penetrated rodent and human brain tissues [5,[8][9][10].…”
Section: Introductionmentioning
confidence: 97%